Reproducible Visualization of Peripheral Lung Lesions With Iriscope - Tebar, Ana Rodríguez; Brindel, Aurélien; Bondue, Benjamin; Leduc, Dimitri; Guibert, Nicolas; Plat, Gavin; Taton, Olivier (Journal of bronchology & interventional pulmonology, 2025)
Iriscope, a miniaturized video-endoscope, was developed to achieve a direct visualization of peripheral nodules unreachable by conventional video-bronchoscopes. The goals of this study were to describe the endobronchial aspect of peripheral lesions, compare it with the final pathologic diagnosis and assess the reproducibility of Iriscope to visualize the endobronchial aspect of peripheral lesions between two observers. In this multicentric observational study, Iriscope was used to visualize peripheral lesions. The endobronchial aspect was compared with the final pathologic diagnosis. Reproducibility was assessed by comparing the blinded interpretations of video recordings by 2 independent observers for each patient. Eighty-four patients with peripheral lesions (24.2 ± 9.8 mm) were included. The final diagnosis confirmed malignancy in 67 (80%) patients. The most frequent endobronchial patterns observed were white plaque (45/84, 54%), obstruction (18/84, 21%) and extrinsic compression (13/84, 15%) with a positive predicted value (PPV) for malignancy of 94%, 90%, and 100%, respectively. The sensitivity and PPV of endoscopy, when any of those 3 patterns were observed, were 73% and 91%, respectively. Iriscope is a reproducible technique that allows for the visualization of peripheral bronchi. White plaque, obstruction, and extrinsic compression patterns described by Iriscope are associated with malignancy.